Treatment of Industrial Textile Wastewater by the Solar Photoelectro-Fenton Process: Influence of Solar Radiation and Applied Current - Salazar-Gonzalez, R; Toledo-Neira, C; Toledo-Neira, C; Vidal-Fuentes, J; Vidal-Fuentes, J; Rivera-Vera, C; Rivera-Vera, C; Sandoval, A; Sandoval, A (Elsevier Ltd, 2019)
This work addresses the removal of Acid Blue 29 (AB29) textile dye by a solar photo-electro-Fenton (SPEF) process. Ten liter AB29 solutions containing 100 mg L−1 total organic carbon (TOC), 0.5 mM Fe2+ and 0.05 M Na2SO4 at a pH of 3.0 were electrolyzed by applying current densities of 25 and 50 mA cm−2 in a pilot plant built in our laboratory. The pilot plant was composed of an electrochemical filter press cell with a dimensionally stable anode (DSA-type) and an air-diffusion cathode coupled to a solar photo-reactor. AB29 was completely mineralized by SPEF at the end of electrolysis, while the solution achieved decolorization in short periods of time on sunny days. Reaction intermediates, such as aromatic compounds, carboxylic acids and inorganic ions, were found during the oxidation process. Solar irradiation favors the mineralization of the dye in cost and efficiency compared to other electrochemical methods. Moreover, the treatment of an industrial textile effluent containing AB29 by SPEF produced mineralization greater than 90% on sunny days. © 2019 International Solar Energy Society